Five questions on the cell-to-cell movement of Orthotospoviruses - Pratibha Singh; Rishi Raj; H.S. Savithri (BBA Advances)
Plant viruses employ Movement proteins (MP) for their cell to cell spread through plasmodesmata (PD). MP modifies the PD and increases its size exclusion limit (SEL). However, the mechanism by which MPs are targeted to the PD is still unresolved and there is a lack of consensus owing to limited studies on their biochemical and structural characters. The non structural protein m (NSm) functions as the MP in Orthotospoviruses. Tospoviral NSm associate with ER membrane. They also form tubules in protoplasts. Groundnut bud necrosis virus (GBNV), a tospovirus, infects several crop plants throughout India and is economically very important. GBNV NSm associates with the membrane strongly via the C-terminal coiled-coil domain, modifies the membrane and causes vesicle fusion in vitro and remodels the ER network into vesicles in vivo. These vesicles are in contrast to the tubules formed by other related tospovirus in cells lacking cell wall. In this review, five important questions on the cell-to-cell movement of tospoviruses have been addressed and based on the various reports, a plausible model on the cell-to-cell movement of Orthotospoviruses is presented.